Immunomodulatory Effects of Taiwanese Neolitsea Species on Th1 and Th2 Functionality - Yin-Hua Cheng; Ying-Chi Lin; Ih-Sheng Chen; Sian-De Liu; Jih-Heng Li; Chia-Chi Wang (Journal of Immunology Research)
Neolitsea species, medicinal plants belonging to Lauraceae, contain rich alkaloids, steroids, sesquiterpenoids, and triterpenoids which possess antimicrobial, antioxidant, and anti-inflammatory bioactivities. However, species differences in the immunomodulatory effects and evidence pertaining to the effects of Neolitsea species on adaptive immunity are scarce. This study aimed to evaluate the immunomodulatory properties of ten Taiwanese Neolitsea plants on T helper (Th) cell functionality, especially Th1 and Th2. Most of the 29 crude extracts of Neolitsea were not toxic to splenocytes, except N. buisanensis roots. N. aciculata and N. villosa leaf extracts possessed differential immunomodulatory effects on Th1/Th2 balance. N. aciculata var. variabillima and N. hiiranensis leaf extracts attenuated both Th1 and Th2 cytokines while N. konishii dramatically suppressed IFN-γ production. As N. aciculata var. variabillima and N. konishii leaf extracts significantly attenuated Th1 functionality, we further evaluated their effects on CD4 cells under CD3/CD28 stimulation. N. aciculata var. variabillima significantly suppressed IFN-γ, IL-10, and IL-17, demonstrating the broad suppressive effects on T helper cells; N. konishii significantly suppressed IFN-γ and IL-10 production, while the production of IL-17 was not altered. Collectively, these data demonstrated that leaf extracts of Taiwanese Neolitsea species contain phytochemicals with potentials to be developed as selective immunomodulators.